Development and Optimization of Efficient Biocatalysts from the Perspective of Green Chemistry - Chen, Zhuo (International Journal of Materials Science and Technology Studies, 2024)
The purpose of this study is to investigate the innovative design and efficiency improvement strategies of biomass catalysts from the perspective of green chemistry. In view of the increasing global awareness of environmental protection and the keen demand for sustainable development models, green chemistry has become an indispensable evolution direction in the field of chemical engineering. Biomass catalysts, with their excellent efficiency, excellent selectivity, and low impact on the environment, have shown great potential applications in the territory of green chemistry. This paper describes how to select specific microbial populations, use gene manipulation technology to breed high-performance recombinant enzymes, and use immobilization technology to enhance their durability and reuse. Experimental experience confirms that the improved biomass catalyst exhibits outstanding catalytic activity and stability, significantly reducing energy consumption while minimizing by-product output. Through the characterization of the catalyst, the catalytic mechanism of the catalyst is discussed and evaluated from the standpoint of green chemistry. These findings not only lay the theoretical foundation for the construction of innovative biomass catalysts, but also light the green light for technical support to further promote more eco-friendly chemical processes. Future work will examine more closely the potential of such biocatalysts in complex industrial ecosystems.